2018
DOI: 10.1177/0971355718810291
|View full text |Cite
|
Sign up to set email alerts
|

Professionalisation of the Family Firm and Its Relationship with Personal Values

Abstract: This study aims to determine the relationships between personal values (PVs) and the professionalisation of family firms. To achieve this objective, the theoretical model of PVs by Schwartz (Advances in Experimental Social Psychology 25:1–65, 1992; Journal of Social Issues 50:19–45, 1994) and the multidimensional model of professionalisation by Dekker, Lybaert, Steijvers and Depaire (Family Business Review 26(1): 81–99, 2013; Journal of Small Business Management 53(2): 516–538, 2015) were used, highlighting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 94 publications
(204 reference statements)
1
34
0
6
Order By: Relevance
“…közi szakirodalomban (Stewart & Hitt, 2012;Dekker, Lybaert, Steijvers, Depaire, & Mercken, 2013;Dekker, Lybaert, Steijvers, & Depaire, 2015;Camfield & Franco, 2019), de jelent meg hazai publikáció is ezen a téren (Németh & Németh, 2018). A professzionalizálódás mint vizsgálati fókusz hosszú múltra tekint vissza a családi vállalkozások kutatásában, mivel a családi cégeket rendszerint szakszerűtlennek, vagy elavult szervezeteknek tüntették fel (Chandler, 1977).…”
Section: Cikkek Tanulmányokunclassified
See 3 more Smart Citations
“…közi szakirodalomban (Stewart & Hitt, 2012;Dekker, Lybaert, Steijvers, Depaire, & Mercken, 2013;Dekker, Lybaert, Steijvers, & Depaire, 2015;Camfield & Franco, 2019), de jelent meg hazai publikáció is ezen a téren (Németh & Németh, 2018). A professzionalizálódás mint vizsgálati fókusz hosszú múltra tekint vissza a családi vállalkozások kutatásában, mivel a családi cégeket rendszerint szakszerűtlennek, vagy elavult szervezeteknek tüntették fel (Chandler, 1977).…”
Section: Cikkek Tanulmányokunclassified
“…A professzionalizálódás elméleti és gyakorlati dimenzióit foglalja össze a következő táblázat a korábban említett kiegészítésekkel (Dyer, 1989;Songini, 2006;Dekker et al, 2013;Basco, 2013;Gimeno & Parada, 2014) és új feltárásokkal (Suess, 2014;Madison et al, 2018;Camfield & Franco, 2019;Polat, 2020). A kiegészített modell magába foglalja a professzionalizálódás eddig feltárt tartalmi dimenzióit a teoretikus, valamint az empirikus elemzések alapján.…”
Section: A Professzonalizáció Multidimenzionális Modelljének Kiegészíunclassified
See 2 more Smart Citations
“…In their research on 249 Portuguese family businesses, Camfield and Franco (2019) confirmed the dimensions of professionalization defined by Dekker et al and suggested adding three new dimensions: (6) family involvement in management systems in parallel with previous research (Dyer, 1989;Gnan & Songini, 2003;Hall & Nordqvist, 2008;Chrisman, Chua, Le Breton -Miller, Miller, & Steier, 2018) the professionalization of a business does not begin with the recruitment of an external, professional manager, but with the training of family members who can also acquire the necessary skills, ( 7) the cultural aspects that are at least as important as financial aspects (Gnan & Songini, 2009;Waldkirch et al, 2017;Polat, 2020) and ( 8) organizational development thus complementing the professionalization of family businesses into an eight-dimensional multidimensional model.…”
Section: Complementing the Multidimensional Model Of Professionalizationmentioning
confidence: 99%